Sidelights on Negro Soldiers - Williams, Charles H. (Charles Halston), 1886-; Brawley, Benjamin Griffith, 1882-1939 (Salt Lake City, UT : Project Gutenberg, 2022)
"Sidelights on Negro Soldiers" by Charles H. Williams is a historical account written in the early 20th century. The book explores the experiences and contributions of African American soldiers during World War I, detailing the conditions they faced both in training camps in the United States and on the frontlines in Europe. The author aims to shed light on their accomplishments and the societal challenges they encountered, providing a critical view of race and military service in America. The opening of the work presents the author's motivation and purpose for writing, discussing his extensive investigation into the lives of Negro soldiers during the war. Williams emphasizes the dual nature of his study: to document the achievements of these soldiers while also addressing the disparities and discrimination they faced. Through personal visits to camps, interviews with soldiers, and consultations with military officials, Williams sets the tone for a revealing examination of not only the military effectiveness of Negro soldiers but also their struggle for recognition and equality in an often prejudiced environment. This opening establishes a foundation for a nuanced discussion about race, identity, and patriotism during a tumultuous period in history. (This is an automatically generated summary.)
Release date is 2022-01-03
Charlene Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: World War, 1914-1918 -- Participation, African American